Offshoring, a threat for the UK's knowledge jobs? Globalisation and the extent and impact of offshore outsourcing - Rüdiger, Katerina (London, 2007)
"Global changes in the location of production and the outsourcing of tasks to low-wage countries have dominated the public discourse for some time. Especially the relatively recent IT boom in India, which has led to some media hype, nurturing a fear in high income countries such as the UK that even relatively high-skilled, well-paid jobs are now also under threat by this next wave of technology driven globalisation."